Pelvic Abscess after Cesarean Section Treated with Laparoscopic Drainage. (11th June 2021) - Murayama, Yumi; Tanaka, Tomohito; Maruoka, Hiroshi; Daimon, Atsushi; Ueda, Shoko; Ohmichi, Masahide
Abstract : Cesarean section (CS), the rate of which is increasing worldwide, may be associated with complications. Although pelvic abscess after CS is rare, it is difficult to treat. We herein report two cases of pelvic abscess treated laparoscopically after CS. The abscesses of the patients were located in the pouch of Douglas and the uterine scar after CS, respectively. Several days after CS, the patients presented with lower abdominal pain and fever. Laparoscopic drainage was performed because imaging revealed a pelvic abscess that was not amenable to drainage through interventional radiology. The patients recovered from infection and were discharged four days after drainage.